Biological activities of Alpinia pahangensis and Alpinia mutica extracts / Fadhlina binti Mahfot - Fadhlina, Mahfot (2011)
The aim of the present study is to investigate the biological activities of two selected wild Alpinia species namely, Alpinia pahangensis Ridl. and Alpinia mutica Roxb. Extraction of the rhizomes and leaves was done successively using three solvents with different polarity: hexane, dichloromethane and methanol. The crude extracts were tested for their antimicrobial and antioxidant activities. The antioxidant activity was determined using the DPPH free radical scavenging method. The antimicrobial activity was investigated based on disc-diffusion assay and minimum inhibition concentration (MIC) against 12 microorganisms consisting of six gram positive bacteria: Bacillus cerues, Bacillus subtilis, Staphylococcus aureus, Streptococus mutans, Streptococcus sanguis and Streptococus mitis (Streptococci species are oral bacteria), three gram negative bacteria: Proteus vulgaris, Pseudomonas aeruginosa and Escherichia coli and three unicellular fungi: Candida parapsilosis, Candida albican and Schizosaccharomyces pombe. The yield of crude extracts from the rhizomes for both species of Alpinia was higher compared to those from the leaves with the highest yield (7.16 %) obtained from the rhizome of A. mutica (methanol extract). In comparing the effect of solvents on crude extract yield, it was found that the increase in yield correlated directly with the solvent polarity except for the leaves of A. pahangensis where the yield was higher (3.16 %) in dichloromethane extract compared with the methanol extract (1.78 %). In the antimicrobial assay, the rhizome hexane and dichloromethane extracts of A. pahangensis showed strong inhibition against gram positive bacteria namely Bacillus cerues and Bacillus subtilis with an MIC value (3120 μg/ml) close to the standard reference, Streptomycin (2500 μg/ml), except for the dichloromethane extract against Bacillus cerues with MIC at 12,500 μg/ml. All extracts failed to exhibit any inhibition against all the tested unicellular fungi and two gram positive oral bacteria namely Streptococus mutans and Streptococcus sanguis. In DPPH free radical scavenging assay, A. pahangensis rhizome methanol extract demonstrated the lowest IC50 value (1.71 mg/ml) but less scavenging activity compared to ascorbic acid (0.085 mg/ml). The results obtained suggest that the antimicrobial compounds in both plants maybe found in the extract of the less polar solvents (hexane and dichloromethane) while the antioxidant compounds, particularly in the rhizomes, maybe found in the extract of the polar solvent (methanol). Therefore, it can be summarized that of the two Alpinia species studied, A. pahangensis showed greater response and potent biological activities compared to A. mutica, which may due to the synergistic effects of the compounds present in A. pahangensis, an unexploited wild ginger species.